2014
DOI: 10.1155/2014/871609
|View full text |Cite
|
Sign up to set email alerts
|

PET Radiopharmaceuticals for Imaging Integrin Expression: Tracers in Clinical Studies and Recent Developments

Abstract: Noninvasive determination of integrin expression has become an interesting approach in nuclear medicine. Since the discovery of the first 18F-labeled cyclic RGD peptide as radiotracer for imaging integrin α v β 3 expression in vivo, there have been carried out enormous efforts to develop RGD peptides for PET imaging. Moreover, in recent years, additional integrins, including α 5 β 1 and α v β 6, came into the focus of pharmaceutical radiochemistry. This review will discuss the tracers already evaluated in clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 83 publications
0
79
0
Order By: Relevance
“…As a proof of concept, we conjugated NMEB and DMEB to c(RGDfK), hereafter referred to as arginine-glycine-aspartic acid (RGD) peptide, for targeting cell surface receptor integrin a v b 3 . This integrin receptor is overexpressed in various malignancies and has a crucial role in tumor angiogenesis (7)(8)(9). We demonstrated that either NMEB-RGD or DMEB-RGD could be of use as an imaging agent and as a radiotherapeutic agent for the treatment of integrin a v b 3 -expressing tumors.…”
mentioning
confidence: 88%
“…As a proof of concept, we conjugated NMEB and DMEB to c(RGDfK), hereafter referred to as arginine-glycine-aspartic acid (RGD) peptide, for targeting cell surface receptor integrin a v b 3 . This integrin receptor is overexpressed in various malignancies and has a crucial role in tumor angiogenesis (7)(8)(9). We demonstrated that either NMEB-RGD or DMEB-RGD could be of use as an imaging agent and as a radiotherapeutic agent for the treatment of integrin a v b 3 -expressing tumors.…”
mentioning
confidence: 88%
“…23) Neubauer et al 24) recently reported on a 68 Galabeled radiotracer based on an aza-glycine derivative of an α 5 β 1 antagonist that was initially characterized by Heckmann et al based on a nonpeptidic tyrosine scaffold. 25) PET imaging of mice bearing an α 5 β 1 -positive tumor and an α V β 3 -positive tumor on each side of the shoulder demonstrated promising results of this peptidomimetic radiotracer for selective imaging of α 5 β 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nanoconstructs for magnetic resonance (MR) imaging or even for multimodal techniques have been developed. [12][13][14][15][16] First, clinical studies employing novel RGD-based scintigraphic probes focus on safety issues, comparability to standard-of-care diagnostics, and the possibility to monitor antiangiogenic therapies. Figure 1 shows the number of publications dealing with integrin imaging in different contexts in the last few decades.…”
Section: Introduction 18mentioning
confidence: 99%
“…12,[18][19][20] This review focuses on recent advances of integrin molecular imaging for cancer diagnosis. First, clinical applications are highlighted, and experimental approaches in preclinical research and multimodal setups are also discussed.…”
Section: Introduction 18mentioning
confidence: 99%